Essentials of Teaching and Integrating Visual and Media Literacy: Visualizing Learning - Baylen, Danilo M (Springer, 2016)
This book focuses on how to effectively integrate the teaching and learning of visual and media literacies in K-12 and higher education. Not only does it address and review the elements and principles of visual design but also identifies, discusses and describes the value of media in learning diverse and challenging content across disciplines. Finally, this book provides a balanced treatment of how visual and media literacies support deep content learning, student engagement, critical thinking, creativity, problem solving, and production.